Effect of seed size and incubation temperature on seed germination of cardamom (Elettaria cardamomum Maton) - SRINIVASAN, M R SUDHARSHAN, R NAIDU, SIDDAGANGAIAH SIDDAGANGAIAH, K (Journal of Spices and Aromatic Crops, 1993)
An experiment was conducted to find out the optimal incubation temperature and ideal season for sowing cardamom (Elettaria cardalilomum) seeds to achieve better and uniform germination. Germination parameters were studied during September-October, December-January and February-March 1989-91. An incubation temperature of 30°C recorded good germination during all the three seasons. However, seeds kept at ambient temperature during September - October resulted in best germination compared to 30°C. There was no significant difference in germination between seed sizes used.